The Interior Design of Public Library with Javanese Neo Vernacular Concept in Yogyakarta City - Reni Mulyo Saputri; Nurhayatu Nufut Alimin (Pendhapa, 2021)
The existence of quality and adequate reading facilities is one of the many factors that can  encourage people's  interest  in  reading.  Based  on  research  at  various  Taman Baca Masyarakat (TBM) in Yogyakarta, it proves that the existence of reading facilities has a positive impact, including increasing interest in reading, empowering the community, being independent in terms of the economy, and others. Yogyakarta as a City of Students and City of Culture has various educational facilities ranging from elementary to tertiary levels. A large number of educational facilities, in particular, has increased the need for libraries as a place to look for references and as an alternative source of knowledge other than formal schools. The study aims to produce an educational and recreational library with modern packaging that considers elements of culture, tradition and local wisdom as the embodiment of Javanese Neo Vernacular concepts. The creative process in this creation uses a functional approach, an ergonomic approach, and a theme approach. The design implementation is translated through the Javanese Neo Vernacular concept which takes ideas from traditional Javanese architecture or more specifically the Joglo house. The elements in the Joglo house that are taken include the layout, site, and building elements that are tailored to the needs of the library. Design with traditional elements is a manifestation of the educational function of the library and modern elements are a means to attract visitors. The addition of exhibition space is an effort to make the library have a recreational function